2020
DOI: 10.1021/acssuschemeng.0c00649
|View full text |Cite
|
Sign up to set email alerts
|

A Bioresponsive System Based on Mesoporous Organosilica Nanoparticles for Smart Delivery of Fungicide in Response to Pathogen Presence

Abstract: Stimulus-responsive release systems for site-specific pesticide delivery are one of the promising strategies to improve the use efficiency of pesticides as well as decrease environmental damage. Herein, a plant disease microenvironment-responsive nanosystem using disulfide-bridged mesoporous organosilica nanoparticles (MONs) as the porous support and calcium carbonate (CaC) as the capping agent was constructed to deliver prochloraz (PRO) for management of Sclerotinia disease. The obtained PRO-MON-CaC had high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…The results showed that the safety of Bup@MSNs@P(NIPAM‐MAA) to aquatic organisms was much higher than that of buprofezin SC. The same phenomenon has been observed in other research 48–50 …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the safety of Bup@MSNs@P(NIPAM‐MAA) to aquatic organisms was much higher than that of buprofezin SC. The same phenomenon has been observed in other research 48–50 …”
Section: Resultssupporting
confidence: 90%
“…Zebrafish, a well‐established model organism for toxicity assessment in vivo , 48 was selected to evaluate the biosafety of Bup@MSNs@P(NIPAM‐MAA). During the entire experiment, no deaths of fish were observed in the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Biopolymeric nanoparticles are systems that can be made from polysaccharides, lipids, and proteins, resulting in nanoparticles that are biodegradable and biocompatible, besides being able to be designed to respond to different environmental stimuli [6,8,9]. These systems can be loaded with various substances, including fungicides [93,94], essential oils [89,95,96], plant growth regulators [54,97,98], and fertilizers [99].…”
Section: Sustained Release Nanocarrier Systemsmentioning
confidence: 99%
“…For example, Gao et al. [ 90 ] showed that mesoporous organosilica NPs used for pesticide delivery, have a longer Sclerotinia disease protection window on plants, which provides a solution for precisely managing plant disease and farming. Appell et al.…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%